Conflict in a paediatric hospital: a prospective mixed-method study. Issue 1 (9th November 2015) - Forbat, Liz; Sayer, Charlotte; McNamee, Phillip; Menson, Esse; Barclay, Sarah
Abstract : Background: Conflict in healthcare is a well-recognised but under-examined phenomenon. Little is known about the prevalence and causes of conflict across paediatric specialties. Objective: To report the frequency and characteristics of conflict in a paediatric hospital. Design and setting: An explanatory sequential mixed-method approach was adopted. A bespoke questionnaire recorded frequency, severity, cause and staff involved in conflict prospectively. Data were recorded for the same two 12-week periods in 2013 and 2014, in one UK children's teaching hospital. Data were analysed using descriptive statistics and correlation, the findings of which informed the construction of a semistructured interview schedule. Qualitative interviews were conducted with six key informant healthcare professionals to aid data interpretation; interviews were analysed thematically. Results: 136 individual episodes of conflict were reported. The three most common causes were 'communication breakdown', 'disagreements about treatment' and 'unrealistic expectations'. Over 448 h of healthcare professional time was taken up by these conflicts; most often staff nurses, consultants, doctors in training and matrons. The mean severity rating was 4.9 out of 10. Qualitative interviews revealed consensus regarding whether conflicts were ranked as low, medium or high severity, and explanations regarding why neurology recorded the highest number of conflicts in the observed period. Conclusions: Conflict is prevalent across paediatric specialties, and particularly in neurology, general paediatrics and neonatology. Considerable staff time is taken in managing conflict, indicating a need to focus resources on supporting staff to resolve conflict, notably managing communication breakdown.